Síntese, caracterização e aplicação de membranas de acetato de celulose a partir da reciclagem da palha de milho em processo de ultrafiltração - Ribeiro, Elaine Angélica Mundim (2013)
In this study corn stover (CS) was used as an alternative source of cellulose for the production of cellulose acetate (CA) in order to produce asymmetric membranes and study their morphologic characteristics and transport properties. CS was previously purified and characterized according to its cellulose content, hemicellulose and lignin. The corn stover cellulose was acetylated and two types of CA with different acetylation degrees were obtained. They were characterized by infrared spectroscopy, differential scanning calorimetry (DSC), termogravimetric analysis (TGA), X-ray diffractometry, and determination of the degree of replacement by chemical route and viscosimetric molecular mass. The obtained corn stover CAs presented a substitution degree of 2.78 and 2.49, thus they were characterized as cellulose triacetate and diacetate, respectively. The properties of the ACs produced from CS were compared with the commercial CA (Rhodia) in the membrane form. These membranes were prepared using the CA/dioxano/acetone system by the inversion of phase method, which led to the formation of asymmetric membranes. The membranes were characterized by scanning electron microscopy (SEM), X-ray diffractometry, DSC and TGA. They were evaluated based on their transport properties by pure water flux and ultrafiltration (UF) trails, which were conducted under a pressure of 100 KPa. In addition, their protein rejection and molar point cut were determined. The micrographs showed different morphologies on the surface and in the porous support due to mainly a difference in the viscosimetric molecular mass and to the degree of substitution of AC used. At the UF trials, the membranes produced from M-TAC/DAC and M-TAC/DAC-Rho polymeric mixture presented pure water flux and protein rejection values higher than 80% for the egg albumin (45kDa). Therefore, these membranes show more adequate characteristics for application in UF processes than the ones produced without the mixture.